2018
DOI: 10.3390/nano8020122
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Diffraction Studies on the Crystallization, Phase Transformation, and Activation Energies in Anodized Titania Nanotubes

Abstract: The influence of calcination time on the phase transformation and crystallization kinetics of anodized titania nanotube arrays was studied using in-situ isothermal and non-isothermal synchrotron radiation diffraction from room temperature to 900 °C. Anatase first crystallized at 400 °C, while rutile crystallized at 550 °C. Isothermal heating of the anodized titania nanotubes by an increase in the calcination time at 400, 450, 500, 550, 600, and 650 °C resulted in a slight reduction in anatase abundance, but an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…An exceptional feature of TiO 2 nanoparticles (NPs) is their photocatalytic activity that enhances the bacterial killing when exposed to UV light [ 7 , 23 ]. TiO 2 NPs tend to exist in three principal forms, namely brookite, rutile and anatase, and it has been reported that the anatase form has a high photocatalytic and antibacterial activity [ 23 , 24 , 25 , 26 ]. A major biomedical application of TiO 2 NPs is to prevent biofilm formation on medical devices that is related to infections and sepsis [ 3 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…An exceptional feature of TiO 2 nanoparticles (NPs) is their photocatalytic activity that enhances the bacterial killing when exposed to UV light [ 7 , 23 ]. TiO 2 NPs tend to exist in three principal forms, namely brookite, rutile and anatase, and it has been reported that the anatase form has a high photocatalytic and antibacterial activity [ 23 , 24 , 25 , 26 ]. A major biomedical application of TiO 2 NPs is to prevent biofilm formation on medical devices that is related to infections and sepsis [ 3 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…The residual Rietveld refinements were 5.62 and ~11.9 for the Rwp and Rexp, respectively. The goodness-of-fit (χ 2 ) of 4.46 shows an acceptable refinement quality [28][29][30][31][32][33]. Table 1.…”
Section: Xrd Rietveld Analysismentioning
confidence: 99%
“…Rietveld pattern-fitting of the XRD pattern was analyzed from the FullProf software and the goodness-of-fit was estimated from the derived Bragg R-factors (RB), expected R-factor (Rexp), and weighted pattern R-factor (Rwp) [28][29][30][31][32][33]. The preferred orientation, peak shape parameters, lattice parameters, scale factor, 2θ0, sample displacement, and pattern background were optimized in the Rietveld refinement to calculate the GNP lattice parameters.…”
Section: Xrd Rietveld Analysismentioning
confidence: 99%
“…The transformation of anatase-to-rutile has been studied for 400–1200 °C [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ], but limited titania thermal-expansion data exist near the transition temperature. Titania thermal expansion has not been studied in detail and the effects of form, crystal structure, synthesis, doping, particles size, surface area, and atmospheric reactions from a high to a transition temperature are unknown.…”
Section: Introductionmentioning
confidence: 99%